Implementation of the Cooperative Learning Model Through the Game of Galah Hadang in the History Learning of Class XII IPS SMAN 1 Sungai Ambawang Students: Implementasi Model Pembelajaran Kooperatif Melalui Permainan Galah Hadang Dalam Pembelajaran Sejarah Peserta Didik Kelas XII IPS SMAN 1 Sungai Ambawang - Rido Septiadi; Andang Fimansyah; Astrini Eka Putri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to find out the planning, implementation, and evaluation of the implementation of the cooperative learning model through the game of Galah Hadang in the history learning of class XII IPS SMAN 1 Sungai Ambawang. The research background is based on the need for learning innovations that are interesting, contextual, and strengthen the values of local character and culture. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, documentation, and literature studies. The interview was the main source, involving 1 history teacher and 5 students of class XII social studies. The results of the study showed that at the planning stage, teachers set integrative goals between history materials and traditional games, adjusting the materials and schedules. In implementation, Galah Hadang was modified to be relevant to the material of the threat of national disintegration, increasing participation and cooperation. Evaluation is carried out through group presentation assignments